Food consumption behavior during the Covid-19 pandemic - Pagliuso, Marcia Estrella; Carrino, Adauto Luiz (Seven Editora, 2023)
The article presents the results and impacts on the population’s food consumption behavior during the Covid-19 pandemic. Changes in routine, psychological aspects and the contribution of the media in this period form crucial points in the decision-making process in choosing food. A bibliographic review of articles on the subject and quantitative research carried out on the Google Forms platform, published by the WhatsApp application, was carried out. The questionnaire presented a sample of 82 respondents from the city of São Paulo, with the objective of ratifying the inclinations presented in the bibliographic review and assisting in the reflection on which prevention strategies can be developed to combat inappropriate habits during the pandemic. The questions were divided into three blocks, punctuating sociodemographic, psychographic and behavioral aspects, totaling 15 questions. The survey showed that a total of 84% of respondents changed their eating routines totally or partially, in addition to indicating a high level of anxiety in the period, leading to the choice of foods harmful to health. DOI:https://doi.org/10.56238/globalhealthprespesc-074